(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2013)
The conodont collection from the nodular limestone beds of the Su Nuargi II outcrop near Domusnovas in SW-Sardinia (Italy) is restudied for the purpose of reassessing the outcrop and updating the conodont collection to the most recent taxonomy. Su Nuargi II is the most important outcrop in the SW of the island exposing Middle Devonian rocks. Forty-five conodont taxa have been identified in the collection, positioning the outcrop within the interval covering the timorensis to latifossatus zones (Lower to Middle Givetian) slightly widening the interpretation of Olivieri (1985). A new morphotype of Polygnathus linguiformis linguiformis is described. The genera Tortodus and Schmidtognathus are identified for the first time in the Middle Devonian of Sardinia. Additionally, a second Middle Devonian outcrop is discovered in the SW of the Island.